Mapping Social Media Marketing and Sustainable Purchase Intention: Brand Engagement, Sustainable Involvement PRISMA-VOSviewer - Wanda Yulia Utami; Didik J. Rachbini; Ririn Wulandari; Mas Wahyu Wibowo (Jurnal Doktor Manajemen (JDM), 2026)
The growing emphasis on sustainability has intensified academic interest in understanding how social media marketing influences sustainable purchase intention, particularly within the sustainable fashion industry. Despite the expanding body of research, existing studies remain theoretically fragmented and often examine social media marketing, brand engagement, and sustainable involvement in isolation. Grounded in the Stimulus–Organism–Response (SOR) framework, this study aims to systematically map and review the scholarly literature on the relationship between social media marketing (stimulus) and sustainable purchase intention (response), with brand engagement and sustainable involvement conceptualized as key organismic mechanisms. Although research in this area is growing, prior studies remain fragmented and lack theoretical integration. Using a PRISMA-based systematic literature review, 60,509 Scopus-indexed records published between 2015 and 2025 were initially identified. Through a rigorous multi-stage screening process based on relevance, construct integration, sustainable fashion context, and empirical completeness, 15 key articles were selected for in-depth analysis. Bibliometric mapping using VOSviewer was conducted to identify thematic clusters, research trends, and phenomenon gaps. The findings show that sustainable purchase intention is centrally positioned in the literature and is influenced by social media marketing primarily through brand engagement and sustainable involvement. Interactive, value driven social media content enhances consumers’ emotional and cognitive engagement with brands, while higher sustainability involvement strengthens intention consistency. Theoretically, this study contributes by advancing the application of the SOR framework through a unified conceptual perspective. Practically, the results highlight the importance of sustainability storytelling, interactive campaigns, and online community-building as effective social media strategies to stimulate sustainable purchase intention.